2018
DOI: 10.1186/s12936-018-2318-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax and Plasmodium falciparum infection dynamics: re-infections, recrudescences and relapses

Abstract: BackgroundIn malaria endemic populations, complex patterns of Plasmodium vivax and Plasmodium falciparum blood-stage infection dynamics may be observed. Genotyping samples from longitudinal cohort studies for merozoite surface protein (msp) variants increases the information available in the data, allowing multiple infecting parasite clones in a single individual to be identified. msp genotyped samples from two longitudinal cohorts in Papua New Guinea (PNG) and Thailand were analysed using a statistical model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 45 publications
2
33
0
1
Order By: Relevance
“…falciparum co-infection dynamics showed that even when this type of data is available, there is limited statistical power to classify a given infection as a re-infection, recrudescence or relapse with a high probability. 36 The prevalence of all Plasmodium species was highest among children 6-10 y of age, as reported elsewhere. 14,37 This result is likely related to the development of immunity that limits clinical symptoms but does not reduce the chance of being infected.…”
Section: Discussionsupporting
confidence: 75%
“…falciparum co-infection dynamics showed that even when this type of data is available, there is limited statistical power to classify a given infection as a re-infection, recrudescence or relapse with a high probability. 36 The prevalence of all Plasmodium species was highest among children 6-10 y of age, as reported elsewhere. 14,37 This result is likely related to the development of immunity that limits clinical symptoms but does not reduce the chance of being infected.…”
Section: Discussionsupporting
confidence: 75%
“…However in these infections, low-density periods also occurred early in infection, with more than 60% of untreated patients experiencing a subpatent period lasting for 1–34 days directly after the initial peak in parasitaemia 16 . In naturally acquired infections, changes in detectability in relation to duration of infection are extremely difficult to measure due to superinfection, where individuals may be repeatedly infected over time with different parasite strains 17 . This makes it difficult to measure the relative densities or durations of different parasite clones without longitudinal genetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Various statistical and mathematical models of P. vivax exist, ranging from models of within host dynamics to global geostatistical descriptions of prevalence [7,27,33-35,37-54]. However, only two publications to our knowledge have formally considered recurrence states on an individual basis [37,55]. Ross et al .…”
Section: Discussionmentioning
confidence: 99%
“…White et al . combined genetic (from a single polyallelic locus) and time-to-event data using a statistical model of parasite clone acquisition and clearance using samples from cohorts in Papua New Guinea and Thailand [37]. The majority of recurrent episodes were asymptomatic and not treated, and the main target of inference was the duration of asymptomatic infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation